2020
DOI: 10.3847/1538-4357/ab7ffe
|View full text |Cite
|
Sign up to set email alerts
|

Choked Accretion onto a Schwarzschild Black Hole: A Hydrodynamical Jet-launching Mechanism

Abstract: We present a novel, relativistic accretion model onto a Schwarzschild black hole. This consists of a purely hydrodynamical mechanism in which, by breaking spherical symmetry, a radially accreting flow transitions into an inflow-outflow configuration. The spherical symmetry is broken by considering that the accreted material is more concentrated on an equatorial belt, leaving the polar regions relatively under-dense. What we have found is a flux-limited accretion regime in which, for a sufficiently large accret… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 56 publications
2
25
0
Order By: Relevance
“…On the other hand, a relationship between the fluid state at infinity and at the sonic point can be obtained by substituting equations (2.15a) and (2.15b) into equation (2.13b). Doing this results in the following cubic equation for hs (see Tejeda et al 2020, Appendix A) (2.16) as well as the corresponding equation for the sound speed…”
Section: Michel Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, a relationship between the fluid state at infinity and at the sonic point can be obtained by substituting equations (2.15a) and (2.15b) into equation (2.13b). Doing this results in the following cubic equation for hs (see Tejeda et al 2020, Appendix A) (2.16) as well as the corresponding equation for the sound speed…”
Section: Michel Solutionmentioning
confidence: 99%
“…Recent works have also studied deviations away from spherical symmetry by introducing large-scale, small-amplitude density anisotropies, finding that even a slight equator-to-poles density contrast can drastically modify Bondi's solution, giving rise to an inflow-outflow configuration consisting of equatorial accretion and a bipolar outflow. The resulting steady-state configuration, dubbed choked accretion, was studied in Aguayo-Ortiz et al (2019) at the Newtonian level and, within a general relativistic framework, in Tejeda et al (2020) and Aguayo-Ortiz et al (2021) for Schwarzschild and Kerr black holes, respectively. In these series of works, it was found that the total mass flux that reaches the central accretor is of the order of magnitude of the corresponding Bondi mass accretion rate, while all the excess flux is redirected by the density gradient as outflow.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the general solution presented in [30], and following on the work of [31] and [32], Tejeda, Aguayo-Ortiz and Hernandez [33] presented a simple, hydrodynamical mechanism for launching astrophysical jets from a choked accretion flow onto a Schwarzschild black hole. This model starts from a spherically symmetric accretion flow onto a central massive object and introduces a deviation away from spherical symmetry by considering a small-amplitude, large-scale density gradient in such a way that the equatorial region of the accreting material is over dense as compared to the polar regions.…”
Section: Introductionmentioning
confidence: 99%
“…This anisotropic density field translates into a pressure-driven force that, provided a sufficiently large mass accretion rate, can deflect a fraction of the originally radial accretion flow onto a bipolar outflow. The threshold value for the accretion rate determining whether the inflow chokes and the launching mechanism is successful or not is found to be of the order of the mass accretion rate corresponding to the spherically symmetric cases discussed by Bondi and Michel. Even though the approximation of a stiff fluid has a rather limited applicability in astrophysics, the mechanism presented in [33] was shown to be valid for more general equations of state by means of full hydrodynamic numerical simulations. Moreover, as discussed in [32], this mechanism is also valid in the context of Newtonian gravity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation